Policy statement of enteral nutrition for preterm and very low birthweight infants. Issue 2 (5th February 2020) - Mizuno, Katsumi; Shimizu, Toshiaki; Ida, Shinobu; Ito, Setsuko; Inokuchi, Mikako; Ohura, Toshihiro; Okumura, Akihisa; Kawai, Masanobu; Kikuchi, Toru; Sakurai, Motoichiro; Sugihara, Shigetaka; Suzuki, Mitsuyoshi; et al.
Abstract: For preterm and very low birthweight infants, the mother's own milk is the best nutrition. Based on the latest information for mothers who give birth to preterm and very low birthweight infants, medical staff should encourage and assist mothers to pump or express and provide their own milk whenever possible. If the supply of maternal milk is insufficient even though they receive adequate support, or the mother's own milk cannot be given to her infant for any reason, donor human milk should be used. Donors who donate their breast milk need to meet the Guideline of the Japan Human Milk Bank Association. Donor human milk should be provided according to the medical needs of preterm and very low birthweight infants, regardless of their family's financial status. In the future, it will be necessary to create a system to supply an exclusive human milk‐based diet (EHMD), consisting of human milk with the addition of a human milk‐derived human milk fortifier, to preterm and very low birthweight infants.